KEBIJAKAN PENGELUARAN PEMERINTAH: ANTARA PERTUMBUHAN EKONOMI DAN PEMERATAAN - Sobandi, Baban (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
Public expenditure policy is one of fiscal policies wich, directly or indirectly, influences economic growth and equity. The indirect influence happens, for example, when an expenditure policy can cause the increase or decrease of private investment through crowdout or crowd-in effects. If government expenditure is allocated to infrastructure, such as communication and transportation, this policy stimulates the growth of private investment. Expenditure policy allocated to consumptive sector will raise the cost of capital, which in turn makes the private investment crowd-out. Indeed, theoretical and empirical studies show that the variety of impacts depends upon the condition of society, degree of wellbeing, andother factors represented by developed and developing countries. Therefore, government has to consider the condition and patterns of allocation in formulating and implementing such policy.